The Effect of Profit and Cash Flow Components on Stock Returns in Automotive Sub Sector Manufacturing Companies and its Listed Componentson Bei - Yusri Johan Pahlawan; Cahyo Pramono; Kasim Siyo (International Journal of Applied Finance and Business Studies, 2022)
Stock return is the return received by the shareholders on the investment that has been made. Many factors that affect stock returns include profit, investment cash flow, operating cash flow and funding cash flow. The present study is a quantitative one using an associative approach, aimed at analyzing the effect of earnings, investment cash flows, operating cash flows and funding cash flows on stock returns of Manufacturing Companies in the automotive subsector and their components listed on the IDX for the period 2014-2020 using time series data. obtained from the financial statements. The research sample consisted of 5 companies during the 8 year research period so that 5 x 8 = 40 observers were obtained. Data collection using documentation method and data analysis using multiple linear regression. The results showed that Profit, Investment Cash Flow, Operating Cash Flow and Funding Cash Flow serentakeously had a significant effect on Stock Return. This is indicated by the F-count (17.197) > F-table (2.48) and sig-p (0.000) < 0.05. Earnings have a significant effect on Stock Return. Investment Cash Flow has a significant effect on Stock Return. Operating Cash Flow has a significant effect on Stock Return. Funding Cash Flow does not have a significant effect on Stock Return. 1. It is recommended that Manufacturing companies in the automotive subsector and their components listed on the Indonesia Stock Exchange pay more attention to aspects that affect Stock Returns so that Stock Returns can be further improved.